Determinants of longevity and success in Lebanese family businesses - Fahed-Sreih, Josiane (2006)
This article explores the characteristics of Lebanese family businesses using a sample of 114 firms and tests various propositions regarding the relationships between correlates of effective succession planning and longevity. Successful family businesses in Lebanon exhibit a variety of responses to the variables that are conducive to success. The findings indicate that older firms are more inclined to use a participatory decision-making process, as evidenced by more reliance on advisory boards. A significantly larger proportion of older firms relative to younger ones holds family meetings and has formal redemption and liquidity plans. Firms in our sample are characterized by liberal attitudes: more than 75% consider female ownership acceptable and more than two-thirds of the firms respond positively to potential female CEOs.